Modern Business Statistics with Microsoft® Excel®, 7th Edition - David Anderson (Cengage Learning, 2020)
Introduce statistical techniques within an application setting as Anderson/Sweeney/Williams/Camm/Cochran/Fry/Ohlmann's MODERN BUSINESS STATISTICS WITH MICROSOFT® EXCEL®, 7E offers a balanced, conceptual understanding of statistics with an integrated focus on the latest Microsoft® Excel®. This best-selling, comprehensive solution clearly presents statistical methodology in real application settings as every statistical procedure is followed by step-by-step instructions and screen images showing how to use Excel® to perform the procedure. For software versatility, Excel Online and R are also covered. 980 Business examples and application exercises -- including 160 new to this edition -- demonstrate how statistical results provide insights into business decisions and problems. Quality problems with unwavering accuracy and a signature problem-scenario approach show readers how to apply statistical methods to business.